2014
DOI: 10.5935/0101-2800.20140029
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological analysis of pre-implantation donor kidney biopsies: association with graft survival and function in one year post-transplantation

Abstract: Pre-transplant chronic kidney alterations did not influence the post-transplantation one-year graft survival, but arteriosclerosis and glomerulosclerosis is predictive of a worse GFR. Delayed graft function and acute rejection are independent prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Several studies have correlated CI with decreased graft survival . Other studies that found no association were able to show a correlation with a composite clinico‐pathologic score . Our KM estimator showed a correlation of CI with graft survival; however, after adjusting for potential cofounders, no association was evident.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Several studies have correlated CI with decreased graft survival . Other studies that found no association were able to show a correlation with a composite clinico‐pathologic score . Our KM estimator showed a correlation of CI with graft survival; however, after adjusting for potential cofounders, no association was evident.…”
Section: Discussioncontrasting
confidence: 67%
“…ATI in literature has been inconsistently associated with DGF, AR, and lower creatinine at various time points posttransplantation. 7,[22][23][24][25][26]28 10,17,46 Other studies that found no association 18,47 were able to show a correlation with a composite clinico-pathologic score. 18…”
Section: Discussionmentioning
confidence: 99%
“…Rezaei et al30 showed that in the Cox model, four factors, including the presence of surgical or other complications, known primary disease, and donor–recipient relationship, had a significant association with patient survival, and seven factors, including the presence of surgical complications, known primary disease, donor–recipient relationship, gender, weight, same side transplanted kidney, and donor’s age, had significant relationship with graft survival 30. Pegas et al’s2 multivariate model found an association with the presence of arteriosclerosis, glomerulosclerosis, acute rejection, and delayed graft function.…”
Section: Discussionmentioning
confidence: 98%
“…This therapy exhibits a good cost/benefit ratio and can elevate the survival and quality of life of patients with ESRD. It has been estimated that the number of cases with chronic kidney disease and requiring a kidney transplant is increasing yearly by 8% in the USA 2. Iran is a pioneer in the Middle East region in performing kidney transplant for patients 3.…”
Section: Introductionmentioning
confidence: 99%
“…Brazil lacks records on how many transplantation centres perform procurement biopsies or post‐reperfusion biopsies. According to published studies, some Brazilian centres perform procurement biopsies in organs from ECDs to evaluate the organ's viability for transplantation and thus as a tool to support the decision to accept or reject an organ …”
mentioning
confidence: 99%